THE EFFECT OF PRESERVATION METHODS ON THE STORAGE OF YELLOW PUMPKIM PUREE - Sarono Sarono; Yatim R. Widodo (Politeknik Negeri Lampung, 2022)
Puree is a fruit paste with a moisture content of about 60% of the process of steaming and crushing the fruit or often called a ready-to-cook (RTC) product. One of the problems of this puree is that high moisture content causes the puree to easily be damaged. The purpose of this study was to determine the effect of storage temperature, addition of sugar, the use of ammonium benzoate to shelf life of pumpkin puree. Treatment of the study were (1) Addition of sugar with level 20%; 30%; 40%; and 50%, (2) addition of sodium benzoate, with level 1,000 ppm, 2,000 ppm, 3,000 ppm, and (3) storage temperature, with room temperature level and cool box. The results showed that (1) Storage at cold temperatures (0-5oC) was more effective to increase shelf life of yellow pumpkin puree compared with addition of sugar and use of ammonium benzoate preservatives, (2), sugar addition to 30% less effective for prolonging life keep the pumpkin puree, (3) The addition of ammonium benzoate to 3,000 ppm can improve the shelf life of the yellow pumpkin puree.